2018
DOI: 10.1016/j.visres.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Attention modulates trans-saccadic integration

Abstract: With every saccade, humans must reconcile the low resolution peripheral information available before a saccade, with the high resolution foveal information acquired after the saccade. While research has shown that we are able to integrate peripheral and foveal vision in a near-optimal manner, it is still unclear which mechanisms may underpin this important perceptual process. One potential mechanism that may moderate this integration process is visual attention. Pre-saccadic attention is a well documented phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 81 publications
4
41
1
1
Order By: Relevance
“…The authors conclude that attention may be a mechanism which facilitates or allows for transsaccadic feature integration. The critical difference with our study and the Stewart and Schütz (2018) study is that the distractor was presented at an unpredictable moment, thus involuntarily redirecting attentional resources to the distractor. In our experiment, it is likely that attentional resources are distributed across the target and distractor, and not necessarily redirected away from the saccade target.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The authors conclude that attention may be a mechanism which facilitates or allows for transsaccadic feature integration. The critical difference with our study and the Stewart and Schütz (2018) study is that the distractor was presented at an unpredictable moment, thus involuntarily redirecting attentional resources to the distractor. In our experiment, it is likely that attentional resources are distributed across the target and distractor, and not necessarily redirected away from the saccade target.…”
Section: Discussionmentioning
confidence: 63%
“…This may be especially useful when visual information needs to be sampled specifically at the intended saccade landing point, rather than the actual saccade landing point. In line with this proposed mechanism, one notable study has found that by redirecting attention by presenting a salient presaccadic distractor, both saccade motor performance and integration of pre-and postsaccadic feature information was impaired (Stewart & Schütz, 2018). The authors conclude that attention may be a mechanism which facilitates or allows for transsaccadic feature integration.…”
Section: Discussionmentioning
confidence: 79%
“…This mislocalization could also result in a decrease of the influence on the presaccadic color. However, given the known role of visual attention in transsaccadic perception (e.g., Stewart & Schütz, 2018a ), we think our findings reflect modulations of hue perception by a change in the locus of presaccadic attention. Due to the presaccadic shift of attention, the presaccadically acquired information can be temporarily stored in visual working memory, allowing for quick transsaccadic integration after the saccade ( Schut, Van der Stoep, Postma, & Van der Stigchel, 2017 ; Steward & Schütz, 2018b ).…”
Section: Discussionmentioning
confidence: 63%
“…The notion that visual attention may be one of the crucial mechanisms driving transsaccadic perception was recently supported by Stewart and Schütz (2018a) . In their study, a salient distractor was presented at variable intervals before the execution of a saccade.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation